PERCEPTIONS AND REPRESENTATIONS OF WORKPLACE BULLYING: A COMPARATIVE ANALYSIS BETWEEN ITALY AND FRANCE - Dassisti, Liliana; Loriol, Marc; Mininni, Giuseppe; Tafuri, Silvio; Bianchi, Francesco Paolo; Loconsole, Pasqua; Grattagliano, Ignazio (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
The aim of this research is to analyse the phenomenon of workplace bullying in two countries: Italy and France and trying to understand the differences among them. The words used to refer to it are respectively "mobbing" in Italy and "harcèlement moral" in France. The research analyse the phenomenon's characteristics through the opinion of an expert sample, belonging to different areas linked to their cultural background. They were selected by the researchers for their expertise and experience on this topic. The tool used was a semi-structured interview conducted in vivo by the researcher. The data resulting were processed as follow: a qualitative analysis was conducted through the production of short synthesis for each interview; a quantitative analysis was conducted through the attempt to standardize the qualitative answers in percentage data. The results shows the existence of different phenomenon's characteristics in the two countries.